Sensationalism - Jean-Jacques Thomas (Studies in 20th & 21st Century Literature, 1981)
Roland Barthes's fascination with discourse is usually considered a glorification of intellectual exchanges, the parade of a virtuoso eager to display his unalloyed dedication to logocentrism. As a consequence, scholars tend to rely on his writings as if they were principally a catalogue for the functional concepts of modernity. The purpose of this article is to show through a close reading of Barthes's latter-day texts that his exhilarating verbal brio is first and foremost a sensuous relationship between the speaking subject and the verbal substance. In his case, this particular relationship generates a discourse akin to physical heroism, thanks to which the subject is able to postpone the debilitating irruption of «intractable reality.» Barthes, as writing subject, transforms what is a mere tool of communication and argumentation into an overwhelming sensuous machine producing a symbolic make-believe, which, in turn, makes him «more and better alive.»
Keywords: Roland Barthes; discourse; intellectualism; logocentrism; modernity; brio; verbal substance; speaking subject; subject; physical heroism; interactable reality; reality; make-believe; alive